2021
DOI: 10.1177/00207640211027211
|View full text |Cite
|
Sign up to set email alerts
|

Psychological wellbeing and mental health amongst medical undergraduates: A descriptive study assessing more than 1,000 medical students in Sri Lanka

Abstract: Background: Studies from around the world have shown higher rates of anxiety, depression, alcohol and other drug use, and burnout in medical students. Aims: The aim of this study was to identify the socio-demographic factors and severity of difficulties Sri Lankan medical students face regarding psychological wellbeing and burnout. Method: This one-off survey used a cross-sectional design, assessing substance use, psychological wellbeing, and burnout using the CAGE, GHQ-12, and OLBI. The survey was open to all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 27 publications
1
11
2
Order By: Relevance
“…Our study demonstrated a relatively low percentage of pharmacological substances abuse/misuse of 7.2%. This remains higher than the what is reported in Sri-Lanka, similar to Italy, but lower than for instance in New Zealand (Almeida et al, 2019; Dahanayake et al, 2021; Rotenstein et al, 2016). While interpreting the latter results, one must bear in mind that the alcohol/pharmacological substance abuse/misuse are a taboo as they may have legal and professional conduct implications.…”
Section: Discussioncontrasting
confidence: 62%
“…Our study demonstrated a relatively low percentage of pharmacological substances abuse/misuse of 7.2%. This remains higher than the what is reported in Sri-Lanka, similar to Italy, but lower than for instance in New Zealand (Almeida et al, 2019; Dahanayake et al, 2021; Rotenstein et al, 2016). While interpreting the latter results, one must bear in mind that the alcohol/pharmacological substance abuse/misuse are a taboo as they may have legal and professional conduct implications.…”
Section: Discussioncontrasting
confidence: 62%
“…As recent large-scale studies demonstrate, the prevalence of anxious and depressive symptoms has reached even higher levels than those identified in pre-pandemic meta-analyses: among 2,778 Turkish medical students, about 90.2% of the participants had depressive symptoms in the major depressive disorder dimension of the in the Patient Health Questionnaire-9 scale, and 44.5% had moderate/severe anxiety symptoms in the Generalized Anxiety Disorder-7 scale (Çimen et al, 2021). Similarly, in Sri Lanka, 62.5% of the 1,097 students were above the cut-off value of the General Health Questionnaire, a screening tool for current mental health problems (Dahanayake et al, 2021). From the students’ perspective, online teaching also has brought both benefits and difficulties during these unprecedented times, as reported in a UK cross-sectional study (Dost et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Medical students have reported that key sources of stress in university include a reduced work-life balance and high academic pressures (Hill et al, 2018). Dahanayake et al (2021) suggest enhancing student-teacher mentorship and implementing mindfulness can increase resilience and wellbeing amongst students. We aim to outline further potential strategies to improve student wellbeing based on our personal experiences as UK medical students.…”
Section: Dear Editormentioning
confidence: 99%
“…We read with great interest a cross-sectional study conducted by Dahanayake et al (2021) which explored the prevalence and associated factors of burnout and mental health disorders amongst medical students in Sri Lanka. In the study, Dahanayake et al (2021) observed signs of mental health issues in 63% of medical students, however only a small percentage of these students had a formal diagnosis and were obtaining necessary treatment and assistance. Furthermore, after admission into medical school, a rise in mental health issues were observed by the authors.…”
mentioning
confidence: 99%
See 1 more Smart Citation